Analysis of the Implementation of Active Learning for MAN 3 Banda Aceh Students during the Covid-19 Pandemic - Ade Ismayani; Habibati Habibati; Syukratun Nufus (International Journal of Education, Information Technology, and Others, 2021)
There has been a change in the implementation of chemistry learning from face-to-face learning to online learning during the Covid-19 pandemic. Teachers and students have tried to adapt to these new conditions in order to be able to carry out active learning. This study used a descriptive study that aims to explore how students carry out chemistry learning during the Covid-19 pandemic. The research subjects were 55 students of Class XI MAN 3 Banda Aceh. Data was collected using an online questionnaire consisting of 18 questions. From the results of data analysis, it was concluded: most of the students were able to carry out active learning in chemistry learning well in the midst of the Covid-19 pandemic. The implementation of an active learning that is applied gets a good category with an average percentage of 76.67%.